The relationship between Europeanisation and policy styles: a study of agricultural and public health policymaking in three EU Member States. Issue 11 (2nd November 2021) - Candel, Jeroen; Parsons, Kelly; Barling, David; Loudiyi, Salma
ABSTRACT: The role of policy styles in policymaking has attracted renewed scholarly interest in recent years. One of the central debates in this literature revolves around the question of how to reconcile archetype national policy styles with considerable differences in modus operandi across policy sectors. A sector-specific feature that is considered a key determinant of the manifestation of archetype national policy styles in the European Union is the degree of Europeanisation of policy sectors. This paper picks up this suggestion by addressing the question of whether and how Europeanisation affects the degree to which features of an archetype national policy style are manifest within a sector. We address this question by exploring sectoral policy styles in agricultural and food-related public health policymaking across three EU Member States: The Netherlands, the United Kingdom (England), and France. Our findings suggest that the degree of Europeanisation of a policy sector does prove an important condition that helps to understand the relationship between national and sectoral policy styles. More specifically, Europeanisation has the strongest effect when sectors face a higher adaptation pressure, i.e., when there is a larger misfit between sectoral regimes and EU-induced institutional demands. We suggest various promising avenues of future research on this relationship.